FRI0519 Systemic Sclerosis Sera Affect in Vitro Angiogenesis, Wound Healing Capacity and Migration of Dermal Blood Microvascular Endothelial Cells: Therapeutic Implications of Cyclophosphamide. (10th June 2014) - Manetti, M.; Borghini, A.; Nacci, F.; Romano, E.; Milia, A.F.; Guiducci, S.; Matucci-Cerinic, M.; Ibba-Manneschi, L.; Weber, E.
Abstract : Background: Systemic sclerosis (SSc) is a complex connective tissue disease characterized by extensive fibrosis and vascular abnormalities. Dermal capillaries are progressively reduced in number with consequent chronic tissue hypoxia insufficiently compensated by angiogenesis. In SSc, clinical studies reported that cyclophosphamide (CYC) treatment may significantly improve nailfold capillary damage. Moreover, our group has recently shown that the beneficial effects of CYC treatment in SSc may be due in part to the normalization of the endothelial cell-matrix interactions. Objectives: In the present study, we evaluated the effects of sera from naïve or CYC-treated SSc patients on the in vitro capacity of human adult dermal blood microvascular endothelial cells (B-MVECs) to perform angiogenesis and to migrate and proliferate in response to injury. Methods: Dermal B-MVECs were challenged with sera from SSc patients (n=21; n=13 limited SSc (lSSc) and n=8 diffuse SSc (dSSc)), treatment-naïve (n=8) or under CYC treatment (n=13), and sera from healthy controls (n=8). Angiogenesis was evaluated after 24 hours of cell seeding on Geltrex (reduced growth factor basement membrane matrix) in endothelial basal medium containing 2% fetal bovine serum and 10% control or SSc serum. The number of branching points was quantified. Wound healing assay was performed on confluent cells grown in 12-well plates and evaluated at 24 hours after wounding. Chemotaxis was assessed by using the Boyden chamber assay. Results: Angiogenesis was significantly reduced upon challenge with sera from treatment-naïve SSc patients compared with healthy controls (p<0.005). Moreover, angiogenesis was significantly lower in the presence of naïve dSSc sera compared with naïve lSSc sera (p=0.02). Upon challenging of B-MVECs with sera from CYC-treated SSc patients, the angiogenic capacity was comparable to that of cells treated with healthy sera. Wound healing capacity was significantly decreased upon challenge with sera from both treatment-naïve and CYC-treated SSc patients compared with healthy controls (both p<0.005), with no difference between naïve and CYC-treated SSc sera. The Boyden chamber assay gave similar findings with significantly lower migration of B-MVECs in the presence either of treatment-naïve SSc or CYC-treated SSc sera compared with healthy sera (both p<0.001). Furthermore, both wound healing capacity and chemotaxis were significantly reduced upon challenge with naïve dSSc sera compared with naïve lSSc sera (p<0.001). Conclusions: Treatment-naïve SSc sera have significant inhibitory effects on angiogenesis, wound healing capacity and chemotaxis of dermal B-MVECs. Moreover, the inhibitory effects of dSSc sera are significantly stronger than those of lSSc sera. Challenge with CYC-treated SSc sera effectively maintained B-MVEC angiogenesis on Geltrex at levels comparable to those of healthy control sera. Conversely, it was not able to specifically restore B-MVEC wound healing capacity and chemotaxis. Therefore, in SSc patients CYC treatment might foster angiogenesis mainly through the normalization of the endothelial cell invasive capacity and cell-matrix interactions. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1905